2020
DOI: 10.1038/s41598-020-74627-3
|View full text |Cite
|
Sign up to set email alerts
|

Porcine circovirus 2 (PCV2) population study in experimentally infected pigs developing PCV2-systemic disease or a subclinical infection

Abstract: Porcine circovirus 2 (PCV2) is a single stranded DNA virus with one of the highest mutation rates among DNA viruses. This ability allows it to generate a cloud of mutants constantly providing new opportunities to adapt and evade the immune system. This pig pathogen is associated to many diseases, globally called porcine circovirus diseases (PCVD) and has been a threat to pig industry since its discovery in the early 90’s. Although 11 ORFs have been predicted from its genome, only two main proteins have been de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 42 publications
3
20
0
Order By: Relevance
“…In contrast, six passages in cell lines did not increase PCV2 mutant spectrum complexity. As per our findings in fetuses, PCV2 genomic diversity and the association of clinical signs with virus diversity have been described in young pigs [35]. Interestingly, all iSNVs that emerged in fetuses in our study were previously reported in young or adult pigs on farms (Table S6), suggesting that in utero-emerging PCV2 variants may reach susceptible populations outside the maternal body, potentially contributing to the heterogeneity of circulating viruses and outbreaks.…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, six passages in cell lines did not increase PCV2 mutant spectrum complexity. As per our findings in fetuses, PCV2 genomic diversity and the association of clinical signs with virus diversity have been described in young pigs [35]. Interestingly, all iSNVs that emerged in fetuses in our study were previously reported in young or adult pigs on farms (Table S6), suggesting that in utero-emerging PCV2 variants may reach susceptible populations outside the maternal body, potentially contributing to the heterogeneity of circulating viruses and outbreaks.…”
Section: Discussionsupporting
confidence: 87%
“…According to some studies, in-host viral quasispecies represent a single selection unit, where selection is not performed based on the individual variant's fitness, but according to the population's mutant distribution 66 , 67 . A recent study tested this hypothesis on PCV2 by monitoring PCV2 variability over time during an experimental infection suggesting an interaction between genetic heterogeneity, immune system response and disease severity 35 . Our research tested a synthetic version of the quasispecies hypothesis using PCV2 for several passages within cells, without the linkage to an immune system of a host.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there are previous studies that aimed to estimate the fitness and dynamics of PCV2 strains in the host (see, for example 35 ). Currently it is very challenging to compare our approach to such studies as our synthetic viruses are completely different to naturally circulating strains that were shaped by evolution in pigs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their single stranded DNA nature and small genomic size, PCV2 viruses have a very high evolutionary rate. In fact, PCV2 viruses have a mutation frequency of around 10 3 –10 4 substitutions/site/year, which is one of the highest rates among DNA viruses and it is at the level of the variation seen in RNA viruses [ 4 ]. This high mutation rate, together with the high rate of recombination (second to PCV2′s propensity for multi-strain or multi-genotype co-infections and infection persistence), immune pressure lead to the genesis of novel and divergent PCV2 variants.…”
Section: Introductionmentioning
confidence: 99%